P212 The DUBLIN Score is a Useful Tool for Predicting Disease Course in Patients with Ulcerative Colitis. (21st January 2022) - Doherty, J; Stack, R; O Morain, N; Mc Namara, D; Coe, C; Kevans, D; Doherty, G
Abstract: Background: The DUBLIN (Degree of Ulcerative colitis Burden of Luminal Inflammation) is a novel simple clinical score of inflammation in patients with Ulcerative Colitis (UC) which can be used easily in outpatients and at the bedside. Methods: We sought to validate the clinical utility of scoring UC inflammatory burden at diagnosis in predicting disease outcomes using the DUBLIN score (DS). We performed a multicentre retrospective study of patients recruited to the Genuity medicine IBD research project at three centres. DS at diagnosis was calculated based on disease extent and endoscopic severity. Study outcomes were need for immunomodulators and/or biologic therapy and need for surgery. We also examined the association between DS and FCP, albumin and C-reactive protein. Results: 679 patients with confirmed UC were identified. 291 had data allowing calculation of DS at diagnosis (median age 38.9 years, 53% male). Median DS was 4 [1–9]. 122 patients were treated with biologic therapy during follow-up. Median DS at diagnosis was significantly higher in patients requiring biologic therapy compared to those not requiring biologic therapy [4 versus 3, p = < 0.001]. Of patients requiring biologic therapy patients with a DS > 3 had a significantly shorter time on 1 st biologic therapy [2.1 versus 3.9 years, p = 0.005]. There was no difference in median DS dependent on immunomodulator use. Similarly median DS at diagnosis was significantly higher in patients requiring colectomy compared to those not requiring colectomy [6 versus 4, p = 0.001]. There was a weak positive correlation between both DS and faecal calprotectin [correlation coefficient 0.27, p = 0.001] and C-reactive protein [correlation coefficient 0.7, p = 0.01] and a weak negative correlation between DS and albumin level [correlation coefficient -0.22, p = 0.04]. Conclusion: Our study validates the clinical utility DS is an accurate clinical tool at diagnosis and during a patients' disease course for identifying disease burden. A higher DS correlates with an increased need for biologic therapy, need for colectomy and increased biomarkers of disease activity. This is a useful tool for day to day use in clinical practise providing personalised management of patients with UC.